Dissemination of COVID-19 in inland cities of Northeastern Brazil. - Sanderson José Costa de Assis; Johnnatas Mikael Lopes; Bartolomeu Fagundes de Lima Filho; Geronimo José Bouzas Sanchis; Thais Sousa Rodrigues Guedes; Rafael Limeira Cavalcanti; Diego Neves Araujo; Antonio José Sarmento da Nóbrega; Marcello Barbosa Otoni Gonçalves Guedes; Angelo Giuseppe Roncalli da Costa Oliveira (PLoS ONE)
Background SARS-CoV-2 causes the new coronavirus disease (COVID-19) and it is weakening all health systems. Therefore, the most vulnerable populations are exposed to harmful consequences, such as illness and death. Thus, this study aims to estimate the temporal effect of COVID-19 dissemination on social indicators of the Northeastern region of Brazil. Methods An ecological time-series study was developed with the following: diagnosed cases of COVID-19 in the largest inland cities of Northeast Brazil, Human Development Index (HDI), poverty incidence, and Gini coefficient. Cities with high HDI, poverty rate, and Gini presented a larger number of patients. Results It was observed by evaluating case trends that COVID-19 spreads unevenly in inland cities of the Northeastern region of Brazil. Conclusions In this sense, we emphasize that regional health managers should support small cities with vulnerable population and social assistance.